Correlation of anatomical variations in chronic sinusitis with diagnostic nasal endoscopy and CT scan of paranasal sinuses: an observational study - Ramesh Babu, G.; Kumar, G. Ravi; Krishna Chaitanya, V. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Drainage and ventilation of paranasal sinuses are important for normal function which depends on effective mucociliary clearance. In present study we tried to emphasize variations in lateral wall of nose and clinical features leading to nose and paranasal sinus disease using diagnostic nasal endoscopy and variations in CT scan of paranasal sinuses. The objectives of the study are to observe various anatomical variations in nose and paranasal sinuses and their clinical presentation using diagnostic nasal endoscopy and CT scan of paranasal sinuses and to compare various anatomical variations in nose and paranasal sinuses. Methods: Present study included 54 patients presenting in Department of ENT, Head and Neck Surgery, during February 2015 to February 2017. Results: Diagnostic nasal endoscopy findings reveal that most common finding was polypoidal changes in nasal mucosa in 36 (66.67%) of patients, followed by mucopurulent discharge in 26 (48.14%), postnasal discharge in 20(37.03%) and 4 (7.40%) patients showed prominent agger nasi cell. CT scan of paranasal sinuses revealed multiple sinus involvement in 41 (75.92%) of patients with partial involvement of sinuses. Complete sinus opacification with pan sinusitis was observed in 9 (16.67%), blockade at osteomeatal complex was observed in 46 (85.18%), paradoxical middle turbinate was observed in 5 (9.25%), Concha bullosa was observed in 12 (22.23%) of patients. Conclusions: Each variation have an anatomic and surgical significance, hence each and every case should be individually studied in detail before undergoing functional endoscopic sinus surgery to maximize patient benefit and to prevent unnecessary complications. Diagnostic nasal endoscopic examination is clinical guide to evaluate disease.